The audible past : cultural origins of sound reproduction - Sterne, Jonathan, 1970- (Durham : Duke University Press, 2003)
Machines to hear for them -- Techniques of listening -- Audible technique and media -- Plastic aurality: technologies into media -- The social genesis of sound fidelity -- A resonant tomb -- Conclusion: Audible futures.
Includes bibliographical references (p. [415]-436) and index.
boek